DETAIL ENGINEERING TEMPAT PEMBUANGAN AKHIR (TPA) REGIONAL PEKALONGAN - Badrus Zaman; Syafrudin Syafrudin; Diah Pratiwi (TEKNIK, 2008)
Regional Final Disposal (Regional Landfill) Pekalongan is place a waste serves 3 surrounding areas. The threeareas that served are Pekalongan City, Pekalongan Regency and Batang Regency. These areas are close enoughso that Regional Landfill concept is suitable to be applied in these areas. This Regional landfill is planned to usethe concept of sanitary landfills. Location of land to be used as Pekalongan Regional Landfill is locatedprecisely at the border village of Sengare-Batursari, District Talun in the administrative area of Pekalongan.The results of this study is the design of a sanitary landfill with landfill leachate channeling system, gasventilation equipment and various other supporting facilities, including weighbridge and procurement ofrequired heavy equipment. Approxymately costs required to build the design is Rp. 88.137.990.883,56